IDEOLOGI HAMAS GERAKAN PERLAWANAN ISLAM - Basyuni, Muhammad Muzammil (Jurnal CMES, 2015)
The Islamic movement in middle east area strongly has influenced the constellation of politic, economics, social and culture in the states of middle east area. For the authority of official goverment in that areas, its existence frequently emerged the relation of contradictory. This article aims to reveal the ideology belongs to one of political Islamic movement in Palestine, Hamas (Charokatu â€˜l-MuqÄwamati â€˜l-IslÄmiyyah). The birth of Hamas movement can not be separate from the similar movement, such as Ikhwanul Muslimin (IM) which was centred on Egypt. The background of the Hamas forming was based on the unsatisfying of some partly palestine people for the struggle diplomatically towards the resistance organizations of Palestine. As the organization that was laid under the shadow of IM, the ideology of Hamas was the incarnation ideology of IM which has the great desire for the standing of Islamic State (ad-Daulatu â€˜l-IslÄmiyyah) of independent Palestine and power state fighting for the freedom and independence of Palestine. The current freedom of Palestine was definited by the movement of Hamas. This movement was demanded to have an ability to build the synergy among the other movements in Palestine to realize the freedom of Palestine people.